25‐Hydroxyvitamin D2/D3 levels and factors associated with systemic inflammation and melanoma survival in the Leeds Melanoma Cohort. Issue 12 (13th December 2014) - Newton‐Bishop, Julia A.; Davies, John R.; Latheef, Faheem; Randerson‐Moor, Juliette; Chan, May; Gascoyne, Jo; Waseem, Saila; Haynes, Susan; O'Donovan, Charles; Bishop, D. Timothy
<x xml:space="preserve">Abstract</x> Lower 25‐hydroxyvitamin D2/D3 levels at melanoma diagnosis are associated with thicker primaries and poorer survival. We postulated that this might relate to the deleterious effect of systemic inflammation as 25‐hydroxyvitamin D2/D3 levels are inversely associated with levels of C‐reactive protein. 2, 182 participants in the Leeds Melanoma Cohort (median follow‐up 7.98 years) provided data on drug exposure, comorbidities and a serum 25‐hydroxyvitamin D2/D3 level at recruitment. Factors reported to modify systemic inflammation (low vitamin D levels, high body mass index, use of aspirin or nonsteroidal anti‐inflammatory drugs or smoking were tested as predictors of microscopic ulceration (in which primary tumors are inflamed) and melanoma‐specific survival (MSS). Ulceration was independently associated with lower 25‐hydroxyvitamin D2/D3 levels (odds ratio (OR) = 0.94 per 10 nmol/L, 95% CI 0.88–1.00, p = 0.05) and smoking at diagnosis (OR = 1.47, 95% CI 1.00–2.15, p = 0.04). In analyses adjusted for age and sex, a protective effect was seen of 25‐hydroxyvitamin D2/D3 levels at diagnosis on melanoma death (OR = 0.89 per 10 nmol/L, 95% CI 0.83–0.95, p < 0.001) and smoking increased the risk of death (OR = 1.13 per 10 years, 95% CI 1.05–1.22, p = 0.001). In multivariable analyses (adjusted for tumor thickness) the associations with death from melanoma were low 25‐hydroxyvitamin D2/D3 level at recruitment (<20 nmol/L vs. 20–60 nmol/L, hazard ratio (HR) = 1.52, 95% CI 0.97–2.40, p = 0.07) and smoking duration at diagnosis (HR = 1.11, 95% CI 1.03–1.20, p = 0.009). The study shows evidence that lower vitamin D levels and smoking are associated with ulceration of primary melanomas and poorer MSS. Further analyses are necessary to understand any biological mechanisms that underlie these findings.